2014
DOI: 10.4067/s0717-97072014000400003
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure and DFT Studies of 4-(1-Benzyl-5-Methyl-1h-1,2,3-Triazol-4-Yl)-6-(3- Methoxyphenyl)pyrimidin-2-Amine

Abstract: The title compound 1, 4-(1-benzyl-5-methyl-1H-1,2,3-triazol-4-yl)-6-(3-methoxyphenyl)pyrimidin-2-amine (C 21 H 20 N 6 O), was synthesized and structurally characterized by elemental analysis, 1 H NMR, 13 C NMR and single crystal X-ray diffraction. The molecular conformation is stabilized by an intramolecular C-H…N hydrogen bond, which generates an S(6) ring motif. In the crystal, molecules are linked by two pairs of inversion-related amine N-H N and C-H N hydrogen bonds, each generating alternate R 2 2 (8) rin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(30 reference statements)
2
4
0
Order By: Relevance
“…These vibrations are comparable with literature data . The asymmetric and symmetric bending vibrations are expected at 1,465–1,440 cm −1 and 1,390–1,370 cm −1 . The asymmetric deformation vibrations were measured in FT‐IR at 1,494 and 1,454 cm −1 and computed in the range 1,514–1,453 cm −1 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…These vibrations are comparable with literature data . The asymmetric and symmetric bending vibrations are expected at 1,465–1,440 cm −1 and 1,390–1,370 cm −1 . The asymmetric deformation vibrations were measured in FT‐IR at 1,494 and 1,454 cm −1 and computed in the range 1,514–1,453 cm −1 .…”
Section: Resultssupporting
confidence: 88%
“…Usually, the C=N stretching vibrations occur in the region 1,600–1,490 cm −1 . These vibrations were computed at 1,586–1,511 cm −1 and measured in FT‐IR/Raman at 1,563 cm −1 /1,598 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…S3. The computed chemical shift values are in good agreement with the experimental and literature [46][47][48][49] values. The highly shielded methyl carbons give the 13 In the 1 HNMR spectrum, the peaks at 2 and 2.16 ppm indicate the protons of methyl groups (H16 and H20) and their calculated values are 2.26 and 2.33 ppm.…”
supporting
confidence: 86%
“…GAP value is the difference between the energies of the frontier orbitals (HOMO-LUMO) and plays a critical role in chemical reactivity, which is related to intermolecular interactions. 76 Previous experimental results 77 revealed that the reinforcement of alginate matrix with dextran sulfate presented the highest insulin EE and one of the lowest particle sizes, compared to the other anionic polymers. Considering theoretical results for the reinforcement polymers, HOMO-LUMO gap ( Figure 7A) and dipole moment values of dextran sulfate were the closest to alginate values (Table 4).…”
Section: Quantum Mechanical Studiesmentioning
confidence: 99%